Analysis of the Studies Done on Laboratories in Turkey - YENER, Dündar; KÖKLÜ, Niğmet; YAMAÇ, Ramazan Ziya; YALÇIN, Seher (Journal of Turkish Science Education, 2020)
The aim of this study is to determine the trend of studies in the laboratory and put the current situation in Turkey. For this purpose, document analysis technique, one of the qualitative research methods, was used in the research. The data group of the research consists of thesis studies on laboratories in our country between 1999-2017. Theses in the fields of science, physics, chemistry, and biology have been determined and themes and sub-themes have been created through the keywords of these theses. Then, frequency tables were created according to the themes and sub-themes created. According to the findings obtained, it was seen that the traditional laboratory approach and inquiry-based laboratory approaches are compared in the studies. It was determined that the studies were done on physics subjects and it was determined that complementary measurement and evaluation studies performed for performance evaluation were used in very few numbers. In addition, it was concluded that the keywords did not give enough information about the studies. In this context, it can be suggested to examine the effectiveness of these approaches according to each other and experiment types by examining the approaches in which students can be more active in laboratories.